Role of Gut and Urinary Microbiome in Children with Urinary Tract Infections: A Systematic Review - Anjali Srivastava; Omprakash Shete; Annu Gulia; Sumit Aggarwal; Tarini Shankar Ghosh; Vineet Ahuja; Sachit Anand (Diagnostics)
Background: The complex interaction between the gut and urinary microbiota underscores the importance of understanding microbial dysbiosis in pediatric urinary tract infection (UTI). However, the literature on the gut–urinary axis in pediatric UTIs is limited. This systematic review aims to summarize the current literature on the roles of gut and urinary dysbiosis in pediatric UTIs. Methods: This systematic review was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. A comprehensive literature search was performed across four databases, including PubMed, Web of Science, Scopus, and EMBASE. All studies published between January 2003 and December 2023 utilizing 16S rRNA sequencing to profile the gut or urinary microbiome in children with UTIs were included. Heat map visualization was used to compare microbial profiles between UTI and control cohorts. The methodological quality assessment was performed using the Newcastle–Ottawa scale (NOS). Results: Eight studies were included in this review. While five studies compared the microbiota signatures between patients and controls, three studies focused solely on the UTI cohort. Also, the gut and urinary microbiome profiles were investigated by four studies each. The consistent loss of microbiome alpha-diversity with an enrichment of specific putative pathobiont microbes was observed among the included studies. Escherichia coli consistently emerged as the predominant uropathogen in pediatric UTIs. In addition to this, Escherichia fergusonii, Klebsiella pneumoniae, and Shigella flexneri were isolated in the urine of children with UTIs, and enrichment of Escherichia, Enterococcus, Enterobacter, and Bacillus was demonstrated in the gut microbiota of UTI patients. On the contrary, certain genera, such as Achromobacter, Alistipes, Ezakiella, Finegoldia, Haemophilus, Lactobacillus, Massilia, Prevotella, Bacteroides, and Ureaplasma, were isolated from the controls, predominantly in the fecal samples. The methodological quality of the included studies was variable, with total scores (NOS) ranging from 5 to 8. Conclusions: The enrichment of specific pathobionts, such as Escherichia coli, in the fecal or urinary samples of the UTI cohort, along with the presence of core microbiome-associated genera in the non-UTI population, underscores the critical role of the gut–urinary axis in pediatric UTI pathogenesis. These findings highlight the potential for microbiome-based strategies in pediatric UTIs. Further studies with larger cohorts, standardized healthy controls, and longitudinal profiling are essential to validate these observations and translate them into clinical practice.